Cosmic Clues from Amaterasu: Blazar-driven Ultrahigh-energy Cosmic Rays? - Saikat Das; Srijita Hazra; Nayantara Gupta (The Astrophysical Journal Letters)
The detection of the Amaterasu event of energy 244 EeV by the Telescope Array, one of the most energetic ultrahigh-energy cosmic rays (UHECRs; E ≳ 0.1 EeV) observed to date, invites scrutiny of its potential source. We investigate whether the nearby blazar PKS 1717+177 at redshift z = 0.137, located within $2\mathop{.}\limits^{^° }5$ of the reconstructed arrival direction, could explain the event under a proton-primary hypothesis. Using a one-zone jet model, we fit the multiwavelength spectral energy distribution of the source, incorporating both leptonic and hadronic cascade emissions from photohadronic interactions inside the jet. Our model supports a cosmic-ray origin of the very-high-energy ( ε _γ ≳ 100 GeV) γ -ray flux and predicts a subdominant neutrino flux, 1 one order of magnitude lower than from TXS 0506+056. Under Lorentz invariance violation, UHECRs escaping the blazar jet above a specific energy can propagate unattenuated over hundreds of Mpc due to an increase in energy loss length for certain parameter choices. In such a scenario, the Amaterasu event can have a plausible origin from this blazar. Our analysis indicates negligible deflection in the Galactic magnetic field, implying a strong extragalactic magnetic field is required. Our findings provide a compelling multimessenger framework linking UHECRs, γ -rays, and neutrinos and motivate targeted searches by current and future high-energy neutrino telescopes during increased γ -ray or X-ray activity of this blazar.